International Financial Statistics, January 2018. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses that for countries that are members of the euro area, the exchange rates shown are expressed in national currency units per SDR or per US dollar through 1998, and in euros per SDR or per US dollar thereafter. Data on members' IMF accounts are presented in the Fund Position section in the country tables and in four world tables. Terms and concepts of IMF accounts and the time series in the country and world tables are explained below. When a country joins the IMF, it is assigned a quota that fits into the structure of existing quotas. Quotas are considered in light of the member's economic characteristics, and take into account quotas of similar countries. The size of the member's quota determines, among other things, the member's voting power, the size of its potential access to IMF resources, and its share in allocations of SDRs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet